Polyunsaturated fatty acids suppress glycolytic and lipogenic genes through the inhibition of ChREBP nuclear protein translocation - Renaud Dentin; Fadila Benhamed; Jean-Paul Pégorier; Fabienne Foufelle; Benoit Viollet; Sophie Vaulont; Jean Girard; Catherine Postic (The Journal of Clinical Investigation, 2005)
Dietary polyunsaturated fatty acids (PUFAs) are potent inhibitors of hepatic glycolysis and lipogenesis. Recently, carbohydrate-responsive element–binding protein (ChREBP) was implicated in the regulation by glucose of glycolytic and lipogenic genes, including those encoding L-pyruvate kinase (L-PK) and fatty acid synthase (FAS). The aim of our study was to assess the role of ChREBP in the control of L-PK and FAS gene expression by PUFAs. We demonstrated in mice, both in vivo and in vitro, that PUFAs [linoleate (C18:2), eicosapentanoic acid (C20:5), and docosahexaenoic acid (C22:6)] suppressed ChREBP activity by increasing ChREBP mRNA decay and by altering ChREBP translocation from the cytosol to the nucleus, independently of an activation of the AMP-activated protein kinase, previously shown to regulate ChREBP activity. In contrast, saturated [stearate (C18)] and monounsaturated fatty acids [oleate (C18:1)] had no effect. Since glucose metabolism via the pentose phosphate pathway is determinant for ChREBP nuclear translocation, the decrease in xylulose 5-phosphate concentrations caused by a PUFA diet favors a PUFA-mediated inhibition of ChREBP translocation. In addition, overexpression of a constitutive nuclear ChREBP isoform in cultured hepatocytes significantly reduced the PUFA inhibition of both L-PK and FAS gene expression. Our results demonstrate that the suppressive effect of PUFAs on these genes is primarily caused by an alteration of ChREBP nuclear translocation. In conclusion, we describe a novel mechanism to explain the inhibitory effect of PUFAs on the genes encoding L-PK and FAS and demonstrate that ChREBP is a pivotal transcription factor responsible for coordinating the PUFA suppression of glycolytic and lipogenic genes.